Management and organisational behaviour - Mullins, Laurie J. (Financial Times Pitman, 1999)
The book presents the interactions among the structure and operations of organisations, the process of management and the behaviour of people at work are the main concerns of the book, while the need for organisational effectiveness and the importance of the role of management as an integrating activity are underlying themes throughout. New to this edition are chapters on organisational learning and on technology. Throughout there is now greater emphasis on international issues, the impact of IT, ethics and social responsibility. Cases and examples have been selected from a variety of organisations - public, private, voluntary and international. Subjects such as power and politics, innovation, learning organisations and empowerment have been given greater prominence. All this is generously supported by short and long cases from the Financial Times and other sources,manager profiles, boxed exhibits and newspaper articles to provide a real-life contex